The Effectiveness of a Behavioral Theory-Based Training Program in Improving Reading, Writing, and Language Skills Among Students with Learning Disabilities - Batayneh, Khitam Ahmad; shnykat, Feryal Abd Alhade (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to identify the effectiveness of a behavioral theory-based training program in improving reading, writing and language skills among students with learning difficulties in Amman Governorate. Methods: To achieve the objectives of the study, a one–group quasi-experimental design was used, with a pre-test and post-test design. Three tests were prepared: the first reading test compriseD twelve questions, the second writing test consisted of twelve questions, and a language test containing 20 categories or items testing two skills, with 10 categories testing the receptive language skill, and the remaining 14 categories testing the expressive language skill. Results: The results of the study showed that there is a statistically significant effect in the post-test design for the effectiveness of a behavioral theory-based training program in improving reading, writing and language skills among students with learning difficulties in Amman Governorate. Conclusions: The study recommends that the Ministry of Education and those in charge encourage teachers in the education sector to employ the behavioral theory-based training programs due to their indispensable role in improving reading, writing, and language skills